A Study of Coagulation Factor Levels in Women during Labour and in Their Newborn Infants - Nossel, H. L; Lanzkowsky, P; Levy, S; Mibashan, R. S; Hansen, J. D. L (Thrombosis and Haemostasis, 1966)
1. Coagulation factors levels were measured in 10 normal mothers and in their infants within 15 min of birth and at 48-96 hrs of age.2. In the mothers the levels of fibrinogen (532 mg/%), factors VIII (196%), IX (130%) and X (122%) were elevated; the levels of prothrombin (107%) and factor V (108%) were normal ; and the level of factor XI (69%) was reduced.3. The infants blood examined within 15 min of birth had a slightly elevated factor VIII level (138%), slightly reduced fibrinogen (195 mg/%) and factor V levels (79%), low levels of prothrombin (55%) and factors IX (27%), X (35%) and XI (32%).4. Blood from the infants at 48-96 hrs of age showed little change from the birth levels of factors V (89%), and VIII (116%) and a slight increase in factor XI level (39%). Four of the infants had received vitamin K1 and had higher levels of prothrombin and factors IX and X than the 7 who had not received vitamin K1.5. These results are compared with those of previous studies and the possible mechanisms underlying the changes is discussed.